2008
DOI: 10.1002/prot.22136
|View full text |Cite
|
Sign up to set email alerts
|

A novel binding pocket of cyclin‐dependent kinase 2

Abstract: The cyclin-dependent kinase 2 (cdk2) is a serine/threonine protein kinase that plays a key role in the cell cycle control system of all eukaryotic organisms. It has been a much studied drug target for potential anticancer therapy. Most cdk2 inhibitors in clinical development target almost exclusively the catalytic ATP-binding pocket of cdk2. However, several five amino-acid peptide inhibitors that are directed towards a non-catalytic binding pocket of cdk2 are reported here. Upon binding to this new pocket loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The network representation (C) and surface model (D) of p7 pocket indicate that Tyr180 (position 4) and Pro271 (position 12) may be the crucial residues for p7 (TL) pocket from CLK1 kinase in the CMGC group. This observation agrees with previous experiments 24,40. 2008 | RSC Adv., 2020,10,[2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015] This journal is © The Royal Society of Chemistry 2020RSC Advances PaperOpen Access Article.…”
supporting
confidence: 94%
“…The network representation (C) and surface model (D) of p7 pocket indicate that Tyr180 (position 4) and Pro271 (position 12) may be the crucial residues for p7 (TL) pocket from CLK1 kinase in the CMGC group. This observation agrees with previous experiments 24,40. 2008 | RSC Adv., 2020,10,[2004][2005][2006][2007][2008][2009][2010][2011][2012][2013][2014][2015] This journal is © The Royal Society of Chemistry 2020RSC Advances PaperOpen Access Article.…”
supporting
confidence: 94%
“…In particular, two double mutants TAALS and LAALS of the wild type Tat peptide TKALG (K41A and G44S) are potent kinase inhibitors that disrupt the Cyclin/CDK complex formation. Specifically, in functional kinase inhibition assays using the C-terminal domain (CTD) of RNA polymerase II as a substrate, we observed an IC 50 of 26.1 μM for TAALS and 4.26 μM for LAALS peptides 12 . Using a series of alanine mutagenesis on CDK2, we demonstrated that these peptides interact with CDK2 directly at a binding pocket near the interface of the Cyclin/CDK complex 6 , a result also obtained by computational docking programs whose docking conformation is displayed in Figure 1A, where two key residues of CDK2, Lys178 and Tyr180, required for the binding interaction are labeled 6 .…”
Section: Resultsmentioning
confidence: 93%
“…For CDK9, the conformation was obtained from PDB 3BLH. We followed the docking procedure exactly as previously described in details by Chen et al, 2008 including all specific parameters used in the simulated annealing 12 . Global dockings of LAALS onto CDK2 and CDK9were performed to locate the binding pockets as shown in Figure 1(A)-(B).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular dynamics simulations of interactions between putative BH3 sequences and anti-apoptotic BCL2 family members were carried out essentially as we have described previously [21] except that GROMACS (Groningen Machine for Chemical Simulations) was used as the modeling software (www.gromacs.org) [22]. The starting coordinates for the simulations of the binding of the 25-mer AVEN and dAven peptides to BCL-xL were based on the BAD/BCL-xL complex (PDB code: 1G5J) [4].…”
Section: Materials and Methodologymentioning
confidence: 99%